(3OjhGf SdjeGf GdMdjs - (3SdjeGf Hf OGhO Hf MjOQ Hf CMeO Hf eMehO GdMSjfj GdMdj,J (B1211 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3CjdGe aj CMRGfg hHcGFg ef cGf eKdj aj YXje HdGFg s
(3BNQgG (B:s
(3bO bjnd Ef nboUQJ Yf bOQce eOMj Ef GdgOGjG Ydi ebOGQ egOjgG Udi GdEdg Ydi CQhGMce hSbi CLOGKce eG HbjJe aj YhGOjgG s
(3fSNI efbhdI Yf fSNI eYXegG HNW GdeDdas
(3jdj GdOjhGf JQLeI eNJUQI dUGMH GdOjhGf heQGK dg aj (B12 (3hQbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B263s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B120 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs